DIAGNOSIS OF PROXIMAL TUBULOPATHY IN CHILDREN WITH HIV INFECTION - Аллахвердиева, Зейнаб (SWorldJournal, 2020)
The publication is devoted to the methods of investigation of proximal tubulоpathy in HIV-infected children